Association of Ascochyta blight with morphological, biochemical and agronomic traits in chickpea - S.P. RAJKUMAR and MAHENDRA PAL, J. KUMAR*, BIRENDRA SINGH, (Indian Phytopathology, 2002)
The leaf glandular hair density was invariably more in resistant parents than in the susceptible parents. The correlation analysis in parents and F. showed a strong negative correlation between hair density and blight score. Resistant parents secreted significantly lesser amount of malic acid as compared to susceptible ones. The association of blight with agronomic traits showed negative correlation between blight disease score and traits such as plant height, number of primary branches, number of secondary branches per primary branch and pods per plant.